Preparation of high-capacitance N, S co-doped carbon nanospheres with hierarchical pores as supercapacitors. (20th November 2018) - Xin, Guoxiang; Wang, MengMeng; Zhang, Wenhong; Song, Jinling; Zhang, Bangwen
Abstract: The N, S co-doped carbon nanospheres with/without hierarchical pores (N, S-HPCNs/N, S-CNs) are prepared by the pyrolysis of polypyrrole and (NH4 )2 S2 O8 with/without F127 as the pore-foaming agent in flowing N2 . The results show that the combination of the hierarchical pores and N, S co-doping improves the electrochemical properties of carbon materials. As a result, the specific capacitance of N, S-HPCNs is as high as 416 F g −1 at a current density of 0.2 A g −1, which is much higher than that of N, S-CNs (138 F g −1 ). At a current density of 10 A g −1, the specific capacitance of 313 F g −1 for N, S-HPCNs is obtained, which keeps a capacitance retention of 75.2%, while the N, S-CNs has only the capacitance retention of 44.2%. After 5000 cycles, the retention ratio of N, S-HPCNs as high as 95.8% is obtained and the columbic efficiency of N, S-HPCNs is close to 100%. The symmetric supercapacitor device assembled using N, S-HPCNs exhibited a high energy density of 18.1 Wh kg −1 at a power density of 100 W kg −1 . The exhibited excellent electrochemical performances of N, S-HPCNs are attributed to a high content of doped heteroatoms N and S and the hierarchical pore structure. Highlights: The N, S co-doped carbon nanospheres with hierarchical pores (N, S-HPCNs) are prepared. The specific surface area of N, S-HPCNs reached 1830.8 m 2  g −1 . The contents of N and S of N, S-HPCNs were 4.29% and 3.38%, respectively. The specific capacitance of N, S-HPCNs reached 416 F g −1 at 0.2 A g −1 . The retention ratio of N, S-HPCNs was 95.8% after 5000 cycles.